A 2500-Yr late Holocene multi-proxy record of vegetation and hydrologic changes from a cave guano-clay sequence in Sw Romania. Issue 3 (May 2015) - Onac, Bogdan P.; Hutchinson, Simon M.; Geantă, Anca; Forray, Ferenc L.; Wynn, Jonathan G.; Giurgiu, Alexandra M.; Coroiu, Ioan
Abstract : We provide sedimentological, geochemical, mineral magnetic, stable carbon isotope, charcoal, and pollen-based evidence from a guano/clay sequence in Gaura cu Muscă Cave (SW Romania), from which we deduced that from ~ 1230 BC to ~ AD 1240 climate oscillated between wet and dry. From ~ 1230 BC to AD 1000 the climate was wetter than the present, prompting flooding of the cave, preventing bats from roosting, and resulting in a slow rate of clay accumulation. The second half of the Medieval Warm Period (MWP) was generally drier; the cave experienced occasional flash flooding in between which maternity bat roosts established in the cave. One extremely wet event occurred around AD 1170, when Fe/Mn and Ti/Zr ratios show the highest values coincident with a substantial increase of sediment load in the underground stream. The mineral magnetic characteristics for the second part of the MWP indicate the partial input of surface-sourced sediments reflecting agricultural development and forest clearance in the area. Pollen and microcharcoal studies confirm that the overall vegetation cover and human land use have not changed much in this region since the medieval times.